The Relations Between the Elements of a Sentence in Utterances of Autistic Children Formulated in the Polish Language - Boksa, Ewa (Respectus Philologicus, 2017)
This paper discusses the problem of syntax skills in children with autism. The main research problem pertained to the course of development of syntax in children with autistic disorders. This study compared the syntactic competence of two autistic boys aged 8 years. The linguistic analysis of the testimonies revealed differences in the way sentences were constructed. Nevertheless, in the messages of both boys errors appeared indicating impaired communication competence. Thus, the goal of the research was an attempt to analyse children’s utterances, taking into account the main types of utterances, their structure and grammatical correctness. The research aimed at finding and capturing other forms of expression, typical for children with autism. The syntax skills of children with autism are not very good. If children construct utterances, these are usually synthetically and grammatically poor sentences. Autistic children are unable to combine the two constituents of a sign into a single whole. In addition, they find it difficult to understand words that have a double meaning, namely literal and figurative. The children form short, incomplete, not very detailed utterances, meager in terms of content.